Psychometric Qualities of the Educational Identity Processes Scale (EIPS) - Christiaens, Annabelle H. T.; Nelemans, Stefanie A.; de Moor, Elisabeth L.; Erentaitė, Rasa; Vosylis, Rimantas; Branje, Susan (Frontiers in Psychology, 2022)
In the educational domain, the development of identity becomes especially salient during school transition phases. To assess the specific identity processes that match the adolescents’ experiences before and after the school transition, the Educational Identity Processes Scale (EIPS) was developed. The present study aimed to test the psychometric qualities of the EIPS by examining its factor structure, the internal and convergent validity of the identity dimensions, and whether the questionnaire was measurement invariant over time. The pre-transition version was tested in a Dutch sample (N = 242 early adolescents) and the post-transition version was tested in a Lithuanian sample (N = 1,268 mid-adolescents). Findings indicated good psychometric qualities for both the pre- and post-transition versions of the EIPS. Additionally, context dependencies were observed, as distance to the transition influenced the meaning of specific identity processes and determined whether specific processes could be considered as part of normative development.